THE ROLE OF PASIMPANGAN IDA RATU GEDE MAS MACALING IN BALINESE RITUAL CULTURE AT BANJAR TINGAS BADUNG REGENCY - I Made Dian Saputra; Ni Kadek Trisna Suryantari; Ni Ketut Tirta Kartika Sari; Ni Kadek Budiastuti; I Wayan Wira Ryandika; I Made Arya Wardika; I Gede Arya Bipatrawan (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
The Pasimpangan Ida Ratu Gede Mas Macaling temple, located at Banjar Tingas, Mekar Bhuwana Village, Abiansemal District, Badung Regency, is one of the temples that has a rich meaning and history in the context of Balinese culture. This temple is dedicated to honoring and worshipping Ida Ratu Gede Mas Macaling, a respected figure in Balinese society. In this study, we conduct an in-depth study of the history and cultural role of the Pasimpangan Ida Ratu Gede Mas Macaling Temple in the lives of Balinese people. The research methods used include literature study, field observation, and interviews with local community leaders, and the mangku of the Pasimpangan Ida Ratu Gede Mas Macaling Temple. Our findings indicate that the Pasimpangan Ida Ratu Gede Mas Macaling Templehas a significant role in maintaining Balinese traditions and cultural values. This study is expected to provide deeper insight into the importance of preserving Bali's rich cultural heritage.